Radiological outcome of hamstring graft after anterior cruciate ligament reconstruction with augmentation of bone marrow aspirate concentrate - Bhamare, D. S.; Nathani, Girish; Shevate, Ishan; Desouza, Clevio; Patil, Amol (International Journal of Research in Orthopaedics, 2021)
Background: Anterior cruciate ligament (ACL) tears are common injuries in the athletic population. Surgical intervention is required for ACL tears as it restores the knee function and it prevents early osteoarthritis. In the recent research there is increasing use of bone marrow aspirate concentrate in orthopaedics. Bone marrow aspirate concentrate (BMAC) provides mesenchymal stem cells progenitor cells and growth factors which has potential benefits in hamstring graft healing after ACL reconstruction. Methods: This was a prospective randomized case control study carried out between May 2017 and June 2020. 30 patients between age group of 18 to 40 years with complete ACL tear were divided into two groups which consisted of the control group in which only ACL reconstruction was done and second group in which ACL reconstruction was done augmenting it with bone marrow aspirate concentrate. For the BMAC group, 3 ml of BMAC was obtained in the operation theatre itself and was injected into femoral tunnel and the tibia tunnel just before portal suturing. MRI was obtained post operatively at 6 months and at 1 year. Graft healing was seen as the time taken for the graft to reach ligamentization phase when the graft became hyper intense or was visualized similar to PCL or the remnant which was preserved during reconstruction in all cases. Results: Most of the patients in which augmentation (86%) was done healed at 6 month as compared to those who were not augmented (13%). Conclusions: BMAC showed faster and better healing of the graft in ACL reconstruction.